New records and noteworthy data of plants, algae and fungi in SE Europe and adjacent regions, 22 - Gordana Tomović; Marko S. Sabovljević; Djordje P. Božović; Pavel Širka; Salza Palpurina; Dimitar Stoykov; Vladan Djordjević; Svetlana Krdžić; Dragana Jenačković Gocić; Danijela Nikolić; Marjan Niketić; Aleksandra Marković; et al. (Comprehensive Plant Biology)
This paper presents new records and noteworthy data on the following taxa in SE Europe and adjacent regions: saprotrophic fungi Coronophora gregaria and Teunomyces cretensis, stoneworts Nitella flexilis and Nitellopsis obtusa, mosses Brachytheciastrum olympicum, Buxbaumia viridis and Taxiphyllum densiflium, monocots Dactylorhiza fuchsii, Hydrocharis morsus-ranae, Poa infirma and Poa jubata and dicots Knautia pancicii and Tozzia alpina subsp. carpathica